2019
DOI: 10.5430/wje.v9n3p67
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Leadership and Teachers’ Intention to Stay: The Mediating Role of Perceived Organizational Support and Psychological Capital

Abstract: This paper aims to explore the mediation effect of psychological capital and perceived organizational support on therelationship between authentic leadership and intention to stay. The structural equation modeling technique was usedto test the hypothesized model. A survey was administered to collect data targeting a sample of randomly selectedteachers working at high schools in Tehran. The results suggest that authentic leadership significantly influencesteachers’ intention to stay, psychological capital, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 68 publications
3
18
0
3
Order By: Relevance
“…According to Aria et al (2019), authentic leadership also contributes to the teaching of teachers. It is recommended that principals take appropriate steps to ensure continuous self-regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Aria et al (2019), authentic leadership also contributes to the teaching of teachers. It is recommended that principals take appropriate steps to ensure continuous self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Luthans and Avolio (2003) state that the attributes of a true leader are being calm, ambitious, positive, flexible, humane, progressive, and someone who emphasizes the growth of their followers' leadership. Thus, authentic leaders are motivated by strong spiritual principles and behave in line with their strongly held beliefs, even under pressure; they are strongly mindful of their opinions, capabilities, and shortcomings, and try to consider how their leadership influences others (Aria, Jafari, & Behifar, 2019). Moreover, Avolio et al (2009) have found authentic leadership to be essential in addressing ethical challenges and building a healthy environmental climate.…”
Section: Authentic Leadershipmentioning
confidence: 99%
“…Li, Zhang, Yan, Wen, & Zhang (2020) with China's nursing population, they identify the influence of POS on job control, job satisfaction and intention to stay. About the last variable, Aria, Jafari, & Behifar (2019) Other studies in the services sector have found relationships with health status. POS is a mitigator of aversive effects of chronic pain on performance (Byrne & Hochwarter, 2006), which may be related to the culture of care that is formed from support, as determined by Payne, Cluff, Lang, Matson-Koffman, & Morgan-Lopez (2018) with a wide American sample.…”
Section: Perceived Organizational Support and The Services Sectormentioning
confidence: 99%
“…In the same context, namely education, it is said that "The foundation of authentic leadership is authenticity". It is indicated by the existence of "1) selfawareness, 2) relational transparency, 3) balanced processing 4) internalized moral perspective" [11]. An authentic leader is illustrated to have empathy showing self-affective response, emotional regulation, perspective taking, and empathy to others [12].…”
Section: Introductionmentioning
confidence: 99%